Comparison of malware detection model using supervised machine learning algorithms / Syamir Mohd Shahirudin - Mohd Shahirudin, Syamir (2022)
Because of various security concerns and cyberattacks, cybersecurity is crucial in today's environment. In addition, malware has evolved quickly in recent years. Machine learning is utilised for malware detection with the advancement of malware analysis. The comparison of malware detection model utilising supervised machine learning techniques is the main goal of this project. The objective of this project is to develop the Windows malware detection model using supervised machine learning in Decision Tree, K-NN and Naïve Bayes, to evaluate the performance of malware detection in term of testing and training of the features selection and to compare the accuracy detection model in all three machine learning algorithms. The Windows malware dataset has been trained and tested by these three machine learning algorithms to get the percentage detection accuracy. Then, the outcomes demonstrated that the best classifier for categorizing our data with 0.96% accuracy is the Decision Tree machine learning algorithm. When comparing the accuracy of a malware detection model, it is excellent if there are numerous machine learning algorithms and more malware datasets included.